Coherent synthesis of heterogeneous system – an ant colony optimization approach - Drabowski, Mieczysław (Studia Informatica. System and information technology, 2007)
The paper presents an innovative approach to solving the problems of computer system synthesis based on ant colony optimization method. We describe algorithm realizations aimed to optimize resource, selection and task scheduling, as well as the adaptation of those algorithms for coherent synthesis realization. We then present selected analytical experiments proving the correctness of the coherent synthesis concept and indicate its practical motivations.